Making Decisions About Purchases Based on Varying Consumer Behavior Concerning Product Quality Evaluations - Rahmayani, Melia Wida; Hakim, Abdul; Hernita, Nita; Riyadi, Wulan (AIBPM Publisher, 2024)
Purchasing is an activity that results in a strategic decision to own an item. To what extent do consumer behavior and product quality influence purchasing choices was the purpose of this research. This object of research is on UD. Putra TS Majalengka Jawa Barat. This technique of analyzing purchase decisions uses a bootstrapping resampling process to determine the hypothesis using SEM-PLS with a second-order approach. This research shows that the two most important factors in shaping consumer choices are consumer behavior and product quality. Described items in this paper tried to overcome the problems that arise in purchasing decisions by offering a conceptual framework to be followed in decisions. Apart from the 2 independent variables affecting the dependent variable Purchasing Decisions, there are additional elements to consider, such as Product Design and Consumer Needs.